Caracterização de Estruturas Sedimentares Biogênicas do Estuário de Itaguaré, Bertioga, SP - Zambon, Mateus José de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Biogenic sedimentary structures are the result of the substrate bioturbation process by infauna specimens. Neoichnology focuses on the study of in situ structures in modern environments, and therefore makes it possible to identify the bioturbator, as well as to recognize the physicochemical parameters of the substrate. In this perspective, the estuary is of fundamental interest, since it presents morphological elements under different hydrodynamic processes such as beach, sandy bars and tidal flat. Additionally, estuaries consist of a morphological element of primary importance for the biodiversity of coastal ecosystems and with wide socioeconomic attributes (eg fishing, recreation and etc.). In order to understand whether the distribution of bioturbations is related to the physicochemical properties of depositional features, this study aims to quantify and classify the biogenic sedimentary structures along the estuarine system and correlate their distribution with physicochemical parameters of the substrate , with emphasis on granulometry, organic matter content, salinity, pH and O2 . In a profile that starts from the beach to the Tidal Plain, the study showed a decrease in the energy of the depositional processes, as well as in the values ​​of salinity, dissolved oxygen and pH in the interstitial water samples. It is also noticed a decrease and worsening in grain selection, increase in bioturbation index and organic matter. It was found that the distribution of bioturbators and structures are mainly related to hydrodynamic factors (such as wave and tide), due to their erosive and depositional potential and therefore directly influence the physicochemical parameters analyzed.

Estruturas sedimentares biogênicas são resultado do processo de bioturbação do substrato por espécimes da infauna. A neoicnologia volta-se ao estudo das estruturas in situ em ambientes modernos, e portanto, possibilita identificar o bioturbador, assim como reconhecer as aos parâmetros físico-químicos do substrato. Nesta perspectiva, o estuário é de fundamental interesse, uma vez que, apresenta elementos morfológicos sob diferentes processos hidrodinâmicos como praia, barras arenosas e planície de maré. Adicionalmente, estuários consistem em elemento morfológico de importância primária para a biodiversidade dos ecossistemas costeiros e com amplos atributos socioeconômicos (eg pesca, recreação e etcrecreação etc.). Com intuito de entender se a distribuição das bioturbações relaciona-se às propriedades físico-químicas das feições deposicionais, este estudo tem como objetivo quantificar e classificar as estruturas sedimentares biogênicas ao longo do sistema estuarino e correlacionar a sua distribuição com parâmetros físico-químicos do substrato, como ênfase para granulometria, teor matéria orgânica, salinidade, pH e O2 . Num perfil que se inicia na praia até a Planície de maré o estudo mostrou diminuição na energia dos processos deposicionais, assim como nos valores de salinidade, oxigênio dissolvido e pH nas amostras de água intersticial. Nota-se também afinamento e piora na seleção dos grãos, aumento do índice de bioturbação e matéria orgânica. Foi constatado que a distribuição dos bioturbadores e das estruturas estão relacionados principalmente a fatores hidrodinâmicos (como onda e maré), devido ao seu potencial erosivo e deposional e por consequência influenciar diretamente nos parâmetros físico-químicos analisados.
Characterization of Biogenic Sedimentary Structures in the Itaguaré Estuary, in Bertioga, São Paulo, Brazil
Keywords: Sedimentologia; Neoicnologia; Infauna; Dinâmica costeira